Characteristics and survival of patients diagnosed with cardiac sarcoidosis: A case series - Brazile, Tiffany L.; Saul, Melissa; Nouraie, Seyed Mehdi; Gibson, Kevin (Frontiers in Medicine, 2022)
Sarcoidosis is a multiorgan system granulomatous disease of unknown etiology that can be debilitating and fatal. In the United States, cardiac sarcoidosis (CS) is diagnosed in 5% of patients with systemic sarcoidosis, however, autopsy results suggest that cardiac involvement may be present in >50% of patients. Currently, there are no gold-standard clinical diagnostic or monitoring criteria for CS. We identified patients with a diagnosis of sarcoidosis who were seen at the Simmons Center from 2007 to 2020 who had a positive finding of CS via cardiovascular magnetic resonance (CMR) and/or endomyocardial biopsy as documented in the electronic health record. Medical records were independently reviewed for interpretation and diagnostic features of CS including late gadolinium enhancement (LGE) patterns, increased signal on T2-weighted imaging, and noncaseating granulomas, respectively. Extracardiac organ involvement, cardiac manifestations, comorbidities, treatment history, and vital status were also abstracted. We identified 44 unique patients with evidence of CS out of 246 CMR reports and 9 endomyocardial biopsy pathology reports. The majority of patients (73% ) had pulmonary manifestations, followed by hepatic manifestations (23%), cutaneous involvement (23%), and urolithiasis (20%). Heart failure was the most common cardiac manifestation affecting 59% of patients. Forty-four percent of patients had documented ventricular arrhythmias. Pharmacotherapy was usually initiated for extracardiac manifestations and 93% of patients had been prescribed prednisone. ICD implantation occurred in 43% of patients. Patients were followed up for a median of 5.4 (IQR: 2.4-8.5) years. The 10-year survival was 70%. In addition to age, cutaneous involvement was associated with an increased risk of death (age-adjusted OR = 8.4: 95% CI 1.14-67.89). CMR is an important tool in the noninvasive diagnosis of CS. The presence of LGE on CMR in a pattern consistent with CS has been shown to be a predictor of mortality and likely contributed to a high proportion of patients undergoing ICD implantation to decrease risk of sudden cardiac death. Additional studies are necessary to develop robust criteria for the diagnosis of CS with CMR, assess the benefit of serial imaging for disease monitoring, and evaluate the effect of immunosuppression on disease progression.